Efeito farmacogenômico in vitro do Astrocaryum aculeatum em células mononucleares do sangue periférico e de câncer de mama - Souza Filho, Olmiro Cezimbra de (2014)
Breast cancer, due to their prevalence in our environment and global public health is a disease subject of numerous contemporary studies. Some of these studies suggest that certain genes related to cell cycle and apoptosis and acting on breast cancer can be modulated by bioactive compounds present in food, such as carotenoids. Fruits are foods rich in carotenoids, however, there is still a large number of species whose anticarcinogenic action was not investigated. This is the case of tucuma (Astrocaryum aculeatum) that is widely consumed, usually by Amazonian population and that recent studies shows antioxidant action. It is a fruit that presents high levels of carotenoids and other bioactive compounds that can act as anticarcinogenic pharmacogenomic modulators. Studies of this fruit are incipient, particularly those focused its potential role in the genesis and physiology of breast cancer. Thus, this research aimed to evaluate the effect of ethanol extracts of tucuma (peel and pulp) in the cyto-genotoxicity in human peripheral blood mononuclear cells (PBMCs). Additionally, the anticarcinogenic effect was evaluated in vitro in the commercial line MCF-7 breast cancer, determining the action on the viability, cell proliferation, modulation of apoptosis and oxidative metabolism. The study was conducted from ethanol extracts of peel and pulp, in which were determined the levels of total polyphenols, flavonoids, tannins, alkaloids by spectrophotometry and levels of beta-carotene, quercetin, rutin, gallic, chlorogenic and caffeic acids, by high performance liquid chromatography (HPLC). For investigation of cyto-genotoxic effects of pulp and peel tucuma extracts were used PBMCs obtained from healthy adults. These cells were grown in controlled conditions and exposed to different concentrations of the extracts for 24 and 72 hours. After these periods, viability analysis was conducted by the spectrophotometric assay of MTT (bromide of 3-(4,5)-dimethyl-2-thiazolyl-2,5-diphenyl-2H-tetrazolium). The levels of caspase-1 protein that is associated with events of programmed cell death (apoptosis/pyroptosis) were determined by enzyme immunoassay ELISA. The genotoxic effects were measured by analysis of DNA fragmentation by fluorometric assay using the DNA Picogreen ® dye that is specific for double-stranded DNA molecules (dsDNA). In this case, treatment with higher genomic damage have lower fluorescence levels when compared to control. To evaluate the genotoxicity was also carried out the DNA Alkaline Comet assay and the evaluation of chromosomal instability (G-band cytogenetic). The concentration of reactive oxygen species (ROS) was assessed by fluorimetric assay of DCFH-DA. Considering the results obtained in the first study, only the anticarcinogenic effect of the pulp extract was evaluated in the second study. Initially, MCF-7 cells grown under controlled conditions were exposed to concentrations from 1 to 1000 μg/mL of the extract, in order to determine the concentration range with greater anticarcinogenic potential. Following MCF-7 cells were exposed to three concentrations of the tucuma pulp extract using as positive control chemotherapy all-trans retinoic acid ATRA (1μM). The choice of ATRA concentration was based on previous studies reported in the literature. The action on cell viability and proliferation was determined by MTT assay after 24, 48 and 72h of exposure to treatments. The effect of the treatments in induced apoptosis was evaluated by analyzing the levels of caspases (1, 3 and 8), by ELISA immunoassay and expression of Bcl-2 and BAX genes via RT-PCR technic. Once the tucuma extract is rich in antioxidants, the effect on oxidative metabolism was also evaluated through the analysis of the modulation of gene expression of antioxidant enzymes superoxide dismutase (SOD) 1 and 2, catalase (CAT) and glutathione peroxidase (GPX) and the activity of these enzymes, using the levels of thiols (protein and non-protein) as an indirect measure of GPX. Statistical comparison between different treatments was performed via ANOVA One-Way and post hoc Tukey test. The results showed that the extracts had high levels of polyphenols and beta-carotene. In the first study, high cyto-genotoxic effect was observed at concentrations > 500 μg/mL. The pulp showed lower cyto-genotoxicity and, therefore, was used to evaluate the anticarcinogenic effect. In the second study, concentrations between 300 to 1,000 μg/mL decreased the viability of MCF-7 cells. Thus, concentrations of 300, 500 and 900 μg/mL were used in further testing. Similarly to ATRA, the extract reduced the viability and proliferation of breast cancer cells (p ≤ 0.01). The action in the viability probably involved apoptotic pathway since there was an increase in the levels of caspases 1, 3, 8, and inhibiting the expression of anti-apoptotic Bcl-2 gene. In general, these results were similar to ATRA. The tucuma, as well as ATRA, caused an imbalance in the oxidative metabolism. However, while the ATRA altered the oxidative balance in both cytosolic level as for mitochondrial level, tucuma acted only in cytosolic level, mainly, via decreasing levels of gene expression and activity of SOD1, CAT and increased levels of lipid peroxidation and proteins carbonylation. The overall results, despite the methodological limitations associated with in vitro studies indicates that the tucuma ethanolic extract has anticarcinogenic effect in breast cancer cells MCF-7 involving potential pharmacogenomics modulation of genes and molecules of the apoptotic pathway and oxidative metabolism. This is the first study reporting anticarcinogenic activity of this fruit, and these results open the prospect of further scientific, epidemiological and clinical interest studies.